2017
DOI: 10.1093/infdis/jix082
|View full text |Cite
|
Sign up to set email alerts
|

Association of Macrophage Inflammation Biomarkers With Progression of Subclinical Carotid Artery Atherosclerosis in HIV-Infected Women and Men

Abstract: (See the editorial commentary by Feinstein and Lloyd-Jones on pages 1343-5.)Background. Monocytes and monocyte-derived macrophages promote atherosclerosis through increased inflammation and vascular remodeling. This may be especially true in chronic human immunodeficiency virus (HIV) infection.Methods. We examined 778 women (74% HIV + ) in the Women's Interagency HIV Study and 503 men (65% HIV + ) in the Multicenter AIDS Cohort Study who underwent repeated B-mode carotid artery ultrasound imaging in 2004-2013.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
65
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(70 citation statements)
references
References 49 publications
4
65
1
Order By: Relevance
“…This study supports previous work demonstrating elevated concentrations of inflammatory biomarkers among HIV controllers and LTNPs compared to HIV‐uninfected individuals . Levels of monocyte activation markers sCD163 and sCD14 have been associated with subclinical atherosclerosis in the MACS, WIHS and other cohorts . Despite elevated concentrations of sCD163 and sCD14 in HIV controllers and LTNPs compared to HIV‐uninfected individuals, we found similar prevalences of carotid and coronary subclinical atherosclerosis.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…This study supports previous work demonstrating elevated concentrations of inflammatory biomarkers among HIV controllers and LTNPs compared to HIV‐uninfected individuals . Levels of monocyte activation markers sCD163 and sCD14 have been associated with subclinical atherosclerosis in the MACS, WIHS and other cohorts . Despite elevated concentrations of sCD163 and sCD14 in HIV controllers and LTNPs compared to HIV‐uninfected individuals, we found similar prevalences of carotid and coronary subclinical atherosclerosis.…”
Section: Discussionmentioning
confidence: 98%
“…Inflammatory biomarker concentrations were collected for an ancillary study among 1281 individuals from MACS and WIHS who had serial carotid ultrasound scans . Characteristics of this cohort have been previously described . Biomarkers were chosen based on their established association with CVD risk .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several physiology studies performed in all-male or predominantly male (>90% male) cohorts have revealed relationships between systemic markers of monocyte activation (sCD163, sCD14) and surrogates of atherosclerotic cardiovascular disease (ASCVD) risk including subclinical carotid artery atherosclerosis(21), aortic inflammation(22) (23), subclinical coronary atherosclerotic plaque(24) (25) (26), and pathologically remodeled coronary atherosclerotic plaque(27) (28). Separate physiology studies among WLHIV have confirmed parallel relationships between systemic immune activation markers and ASCVD risk surrogates, including subclinical carotid atherosclerosis(29) (30) (31) and the percent of non-calcified coronary atherosclerotic plaque(32). Cells of monocyte/macrophage lineage may also engender myocardial edema and fibrosis, presaging diastolic dysfunction and heart failure with preserved ejection fraction(33) (34).…”
Section: Sex-specific Mechanisms Underlying Heightened Cvd Risk Amongmentioning
confidence: 94%
“…The extent to which these processes are synergistic and the mechanisms are largely unknown; however, it is possible they explain some of the extrahepatic manifestations of liver disease (and these viral infections). For example, cardiovascular disease incidence appears to be increased with HIV and HCV infection as well as nonalcoholic fatty liver disease (NAFLD), and macrophage activation has been linked to coronary and carotid artery inflammation . Clearly more work is needed to disentangle these associations and particularly to guide approaches to reducing the residual risk of inflammation that appears to be present in persons on long‐term ART.…”
Section: Pathogenesis/immunobiology Of Liver Disease In Patients Infementioning
confidence: 99%